Motivational Messages On Quarter-Life Crisis (QLC) Anxiety Management Among @Najwashiahab Instagram Followers - Nufindra, Ardin; Marta, Rustono Farady; Sarasati, Fitri; Engliana, Engliana; Umar, Umar (KOMUNIKA, 2024)
This current research discusses motivational messages on YouTube content on the issue of anxiety management at the quarter-life crisis (QLC) stage among Instagram followers @NAJWASHIHAB. Motivational messages on YouTube have influenced the audience's enthusiasm after watching the show based on extrinsic and extrinsic motivations. The research utilizes quantitative approach through the use of survey method. The survey data is the followers of the @NAJWASHIHAB Instagram account on quarter-life crisis topic discussion. The results show that the created content influenced the viewers or subjects. The findings indicate that there were positive reactions shown by the content viewers after watching the video "Quarter Life Crisis, Says Abi Quraish Shihab | Shihab & Shihab” on YouTube. The @NAJWASHIHAB Instagram followers demonstrate the ability to manage quarter-life crisis anxiety by practicing mindfulness by being conscious of their environment and openly accepting their emotions.